2016
DOI: 10.1542/peds.2015-1949
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Toddlers Born Very Preterm

Abstract: OBJECTIVE: This study aimed to determine the prevalence of autism spectrum disorder (ASD) by using the Autism Diagnostic Observation Schedule-Generic (ADOS-G) classifications in children born very preterm during their toddler years. METHODS:Two birth cohorts of toddlers (2 and 4 years old) each recruited over 12 months and born at <29 weeks' gestation were administered the Modified Checklist of Autism in Toddlers-Follow-up Interview (M-CHAT-FI) screen, the ADOS-G, and developmental assessments. The ADOS-G was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…Preterm neonates are reported to be at high risk for autism spectrum disorder (Fevang et al, 2016, Limperopoulos et al, 2008, Pritchard et al, 2016), with brain alterations in socio-emotional networks during neonatal period. (Padilla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm neonates are reported to be at high risk for autism spectrum disorder (Fevang et al, 2016, Limperopoulos et al, 2008, Pritchard et al, 2016), with brain alterations in socio-emotional networks during neonatal period. (Padilla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, although these rates are higher than the 9% generally reported in unselected samples,30 33 the true proportion with ASD is likely to be lower as infants may screen positive due to the range of neurodevelopmental impairments commonly observed after EP birth rather than autistic features per se 31 32 34. Where the M-CHAT follow-up interview is used to improve specificity, as prescribed by the authors, a positive screen rate of 13% has been reported in EP infants and a 1.8% prevalence of diagnoses at 2–4 years 35. The M-CHAT is therefore likely to identify children at risk for a range of developmental disorders and should be used with caution when screening for ASD until its predictive validity for later diagnoses is ascertained.…”
Section: Outcomes In Childhood and Adolescencementioning
confidence: 99%
“…Although the prevalence of ASD is 1 to 2% in the general population, 6,7 the prevalence in preterm children is several magnitudes higher (1.8 to 8% 811 ). Sensory, motor, and cognitive impairments, 1113 as well as emotional/behavioral dysregulation, 14 which can affect the validity of the M-CHAT, occur more often in very preterm toddlers than term children.…”
mentioning
confidence: 99%
“…Sensory, motor, and cognitive impairments, 1113 as well as emotional/behavioral dysregulation, 14 which can affect the validity of the M-CHAT, occur more often in very preterm toddlers than term children. Therefore, misclassification rates might be higher among preterm children with such deficits.…”
mentioning
confidence: 99%